The usage of probabilistic assessment for cost calculations of using NPP with hydrogen industrial production - Yu. A. Kolbantcev; M. V. Konyushin; A. A. Kalyutik (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. This study focused on the probability of construction of dual – purpose nuclear-hydrogen unit for cogeneration of hydrogen and electricity with nuclear power reactor VVER-1200 based on AES-2006 project. METHODS. The aim of the study is the probation of the IAEA calculation method originated for sea water desalination unit using nuclear power plant as an energy source, but with a view to same time production of high-quality hydrogen and electricity concerning the ecological issues of hydrogen generation. In particular, the method was used for probabilistic assessment of single-purpose NPP unit and dual-purpose nuclear-hydrogen unit. The supposed result of the study was construction of special building for the electrolytic process purposes. The ground location of the building was out of the main building area. The special building should consist of electrolytic units, technological water feed and removal pipelines, tanks for hydrogen and other service equipment. RESULTS. The paper introduced the theoretical possibility of hydrogen production on the rate up to 1,927∙108 m3/year in the case of full-time basis operation of 50 hydrogen units. The rate of produced hydrogen corresponds to 18,53% of inner Russian market hydrogen needs. In this case the electricity cost factor was 0,097 $/kW∙hr, the cost factor of higher quality hydrogen was 0,956 $/m3. The paper introduced the prime cost comparison of produced hydrogen according to hydrogen units total capacity and arrangement demands. CONCLUSION. This method has the limits of applicability, but in our case, it can be used to calculate key economic factors of the project and to analyze the validation of the energy source and the hydrogen unit size.